Puzzles, mazes, and numbers - Snape, Charles; Scott, Heather (Cambridge : New York : Cambridge University Press, 1995)
This book consists of most of the material from How puzzling, How amazing and How many? by the same authors. It contains fascinating information about numbers and mazes, both historical and modern, with a large number of puzzles, problems and investigational activities. There are solutions and hints to some of the problems at the end of the book
Keywords: Mathematical recreations; Maze puzzles